Microplastics Occurrence in Waters off the Northwest Coast of Peninsular Malaysia: A Spatial Difference - Mohamad Najihah; Mohamad Saupi Ismail; Chee Kong Yap; Ku Kassim Ku Yaacob (Journal of Basic & Applied Sciences, 2020)
Microplastics pollution has been receiving extensive attention globally with its presence felt in both remote and pristine coastal marine environments. Defined as plastics with diameters of 5mm or less and originating from primary and secondary sources, its impact is still not fully understood. Our investigation was conducted along two northern states in Peninsular Malaysia, i.e. Pulau Pinang and Kedah, to quantify microplastics occurrence in the surface waters. Seawater samples were collected from different sampling stations using a 355µm manta net. The plastics was removed from the water samples by density separation, treated with hydrogen peroxide and were identified using a stereo microscope. Microplastics occurred at all sampling stations with numbers varying from 8 to 73 particles/L. Samples were dominated by fragment and filament shapes. Sizes (2 to 3mm) and white colouration were found to be dominant. Future research is suggested to the identification of polymer type and a better understanding of its impact on marine communities.